Gender diversities and sex education. Issue 5 (8th September 2022) - Mayo, Cris
Abstract: This article suggests that science‐based understandings of sex and gender can improve sex education by inviting students to consider what sex and gender mean and by encouraging recognition and respect in a gender‐diverse context. In addition, decolonising approaches to gender provide another route to sexuality education that is more attendant to difference and diversity, helping students to see how culturally embedded and resistant meanings and practices have shaped understandings of gender. Together, these divergent approaches—gender science and decolonising education—provide an array of conceptual links between gender identity and other forms of innovation and reclamation. Such tactics of conceptual connection may help sex education to think about gender in different ways, some of which invite gender‐diverse students into the curriculum and some of which invite normatively gendered students to consider their own complexities. Using these tactics of conceptual linkage encourages educators and students to develop a fuller vocabulary for addressing how gender, sexuality and struggles over meaning can be a core part of sex education. By thinking and teaching more carefully about the diversities related to key concepts like gender, sex education can both critically examine inequities and aim towards the possibilities of gender diversity.